Striving to Implement Green Human Resource Management (GHRM) Policies and Practices: A Study from HR Managers Perspective (FMCG Sector) - Hussain, Faizan; Saifuddin, Qusai; Khan, Iqbal Uddin (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
The purpose of this research is to explore the implementation of Green Human Resource Management practices and policies by the FMCG manufacturing companies of Pakistan. The researchers have enlightened various Green HRM strategies, initiatives, and practices that HR managers have undertaken in their respective organizations. Also, this research highlights the significance of Green HR practices and policies in employee retention, organizational citizenship behavior, and overall organizational image. This research is exploring the perception of Green HR from the HR professionals associated with FMCG companies of Karachi. For this purpose, in-depth interviews were taken by the HR managers of targeted companies to explore the implementation of HR practices and policies in Pakistan. The interview was conducted with the help of an interview protocol, consisting of various open-ended questions based on research objectives and research questions. The findings of this research suggest that the concept of Green HR practices and its benefits that an organization can gain by implementing such practices is vague among the HR professionals of Pakistan. The research has identified the need to train the managers regarding the Green HR initiatives and develop awareness campaigns which guide the managers about the significance that green practices have on the overall organizational performance and its image in the industry.